2021
DOI: 10.1038/s41598-021-91672-8
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor neurons in the bed nucleus of the stria terminalis exhibit sex-specific pain encoding in mice

Abstract: The bed nucleus of the stria terminalis (BNST) plays an emerging role in pain regulation. Pharmacological studies have found that inhibiting corticotropin-releasing factor (CRF) signaling in the BNST can selectively mitigate the sensory and affective-motivational components of pain. However, mechanistic insight on the source of CRF that drives BNST responses to these harmful experiences remains unknown. In the present study, we used a series of genetic approaches to show that CRF in the BNST is engaged in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…For the functional validation of this construct, each of these viruses were mixed in a 4:1 ratio with AAV8-Ef1a-double floxed-hChR2(H134R)-mCherry-WPRE-HGHpA (Addgene; Watertown, MA, USA) and injected with 300 nL per side. To selectively knock down CRF expression in the ventral BNST (26), CRH-flox mice were injected with either AAV8-hSyn-GFP or AAV8-hSyn-Cre-GFP (UNC Vector Core).…”
Section: Stereotaxic Surgerymentioning
confidence: 99%
“…For the functional validation of this construct, each of these viruses were mixed in a 4:1 ratio with AAV8-Ef1a-double floxed-hChR2(H134R)-mCherry-WPRE-HGHpA (Addgene; Watertown, MA, USA) and injected with 300 nL per side. To selectively knock down CRF expression in the ventral BNST (26), CRH-flox mice were injected with either AAV8-hSyn-GFP or AAV8-hSyn-Cre-GFP (UNC Vector Core).…”
Section: Stereotaxic Surgerymentioning
confidence: 99%
“…Previous calcium imaging experiments in BNST-Crh neurons demonstrated that these cells respond to painful stimuli (Yu et al, 2021) and restraint stress (Luchsinger et al, 2021). In response to an acute noxious stimulus BNST-Crh neurons responded with approximately equal numbers having increased or decreased calcium signals (Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the role of CRF in BNST neurons in Part fear, we used a viral approach to genetically knockdown CRF in the BNST 40 . To do this, we injected an AAV encoding cre recombinase or GFP bilaterally into the BNST of CRF lox/lox mice 40 three weeks prior to behavior testing (Figure 3A-C).…”
Section: Crf Knockdown In the Bnst Potentiates Partially Reinforced F...mentioning
confidence: 99%